IMPLEMENTATION OF FISCAL SECURITY IN THE CONTEMPORARY CONDITIONS OF INTERCONNECTEDNESS OF THE WORLD ECONOMY - Lutsyshyn , Z. O.; Katrych , O. D. (The actual problems of regional economy development, 2024)
The article investigates the essence and challenges of ensuring financial security, particularly fiscal security of states, in the context of the transformation of the global economy. A fundamental analysis was conducted, allowing for the formulation of hypotheses and the ranking of countries based on their level of development. The evolution of the concept of state security is examined, and the theoretical approaches of different countries to defining the essence and methodology of financial security calculations are summarized. It is noted that an integral component of financial security is fiscal security, as achieving stability in this area under conditions of economic instability is a criterion for the state's condition. Fiscal security is also a measure of the population's living standards and an indicator of the successful implementation of the state's strategic priorities. For the analysis of fiscal security, the methodology defined in the legislation of selected countries was used. It is mentioned that while financial security indicators are similar across countries, their values differ, so a "normal" step was calculated for each country. It was found that the level of fiscal security affects the macroeconomic stability and economic growth of states. Specifically, countries with a high level of fiscal security demonstrate more stable economic indicators and a lower risk of financial crises. The statistical analysis included a comparison of key fiscal security indicators such as public debt, budget deficit, tax burden, and budget revenues. For example, in 2022, Germany's public debt level was 69% of GDP, the budget deficit was 3.5%, the tax burden was 40%, and budget revenues were 1.5 trillion euros. In Sweden, public debt was 39% of GDP, the budget deficit was 1.8%, the tax burden was 44%, and budget revenues were 0.9 trillion euros. The research results showed that countries with a more efficient fiscal security management system have a higher level of socio-economic development. For example, EU countries such as Germany and Sweden demonstrate a high level of fiscal security due to transparent tax systems and effective public finance management. Therefore, ensuring fiscal security in the context of the transformation of the global economy and its increased interconnectedness at the present stage is a key factor for the stable development of states. This study emphasizes the importance of adapting fiscal security assessment methodologies to modern economic conditions and developing strategies aimed at increasing the resilience of states to economic challenges.